Endometriosis and gestational diabetes mellitus risk: a systematic review and meta-analysis. (4th May 2018) - Pérez-López, Faustino R.; Martínez-Domínguez, Samuel J.; Viñas, Andrea; Pérez-Tambo, Raquel; Lafita, Alberto; Lajusticia, Héctor; Chedraui, Peter; ,
Abstract: Objective: To perform a systematic review and meta-analysis regarding endometriosis and the risk of gestational diabetes mellitus (GDM). Methods: We carried out a search of the following databases: Medline, Embase, Web of Science, Cochrane Library, Scopus, Scielo, Clinicaltrials.gov, the UK Clinical Trials Gateway, and the Australian New Zealand Clinical Trials Registry, from inception through April 28 2017, without language restrictions, in order to evaluate the effect of endometriosis over GDM risk, in women with and without endometriosis. Odds ratios (ORs) and their 95% confidence intervals (CIs) or mean differences (MDs) were calculated as effects. Methodological quality of evidence was assessed with the Newcastle–Ottawa Scale, and heterogeneity among studies with the I 2 statistic. Random-effects models were used for meta-analyses, and publication bias was assessed with Egger's test. Results: We identified 12 studies (10 cohort and two case control studies) with a total of 48, 762 pregnancies, including 3, 461 with endometriosis. Endometriosis had no significant effect on GDM risk (OR =1.14; 95% CI: 0.86, 1.51; p = .35, I 2 = 56%, Egger's test p = .45). Secondary outcomes (gestational age at delivery, birthweight, and Neonatal Intensive Care Unit admission) were statistically similar in women with and without endometriosis. Conclusions: Better-designed studies are needed to confirm our results.